Characterization of Dolomite and its suitability as a raw material for soap production - Mohd Azizi Azanul Mohamad Rapi (Universiti Malaysia Perlis, 2008)
This study is about characterization and soap production by using dolomite as a raw material. Calcium hydroxide and magnesium hydroxide also have been used in this study as a raw material. Soap are made from fats and oil especially palm oil by treating them chemically with strong alkaline solution. Dolomite has been sieve until 0.063 mm sieve size and high temperature is used to heat the dolomite in the furnace. The characterization methods that used in this study are X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM). The pH testing was carried out after heating process to determine the alkaline pH of dolomite. When heated, the reaction between fatty acids and alkaline solution from dolomite will produced calcium soap. This soap has potential to use as grease especially for inhibitor for corrosion.